Ein System zur aggregierten Visualisierung verteilter Materialflusssimulationen - Suess, Tim; Fischer, Matthias; Huber, Daniel; Laroque, Christoph; Dangelmaier, Wilhelm (Augmented & Virtual Reality in der Produktentstehung)

Creating Butterflies in the Core – A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009)

Modeling obstacles in INET/Mobility framework: motivation, integration, and performance - Lichte, Hermann S.; Weide, Jannis (Proceedings of the Second International ICST Conference on Simulation Tools and Techniques)

Design considerations for a network of information - Ahlgren, Bengt; Vercellone, Vinicio; D'Ambrosio, Matteo; Marchisio, Marco; Marsh, Ian; Dannewitz, Christian; Ohlman, Börje; Pentikousis, Kostas; Strandberg, Ove; Rembarz, René (Proceedings of the 2008 ACM CoNEXT Conference on - CONEXT '08)

Planar Visibility Counting - Fischer, Matthias; Hilbig, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Ziegler, Martin (Proc. 25th European Workshop on Computational Geometry)
For a fixed virtual scene (=collection of simplices) S and given observer position p, how many elements of S are weakly visible (i.e. not fully occluded by others) from p? The present work explores the trade-off between query time and preprocessing space for these quantities in 2D: exactly, in the approximate deterministic, and in the probabilistic sense. We deduce the EXISTENCE of an O(m^2/n^2) space data structure for S that, given p and time O(log n), allows to approximate the ratio of occluded segments up to arbitrary constant absolute error; here m denotes the size of the Visibility Graph--which may be quadratic, but typically is just linear in the size n of the scene S. On the other hand, we present a data structure CONSTRUCTIBLE in O(n*log(n)+m^2*polylog(n)/k) preprocessing time and space with similar approximation properties and query time O(k*polylog n), where k<n is an arbitrary parameter. We describe an implementation of this approach and demonstrate the practical benefit of the parameter k to trade memory for query time in an empirical evaluation on three classes of benchmark scenes.

Überlegung zur Senkung des Energieeintrags bei der Compoundierung - Hallmann, Tobias; Schöppner, Volker; Fiekens, Nicolas; Zimmer, Detmar (VDI-Fachtagung Aufbereitungstechnik)

Methodische Modularisierung komplexer Produktstrukturen - Fiekens, Nicolas; Zimmer, Detmar (Konferenz Variantenmanagement im Produktentstehungsprozess im Maschinen- und Anlagenbau)

An Orchestration as a Service Infrastructure using Grid Technologies and WS-BPEL - Höing, Andre; Scherp, Guido; Gudenkauf, Stefan; Meister, Dirk; Brinkmann, André (Proc. Int. Conf. on Service Oriented Computing (ICSOC))

Providing Scientific Software as a Service in Consideration of Service Level Agreements - Niehörster, Oliver; Birkenheuer, Georg; Brinkmann, André; Blunk, Dirk; Elsässer, Brigitta; Herres-Pawlis, Sonja; Krüger, Jens; Niehörster, Julia; Packschies, Lars; Fels, Gregor (Proc. Cracow Grid Workshop (CGW))

Connecting Communities on the Meta-Scheduling Level: The DGSI Approach! - Birkenheuer, Georg; Carlson, Arthur; Fölling, Alexander; Högqvist, Mikael; Hoheisel, Andreas; Papaspyrou, Alexander; Rieger, Klaus; Schott, Bernhard; Ziegler, Wolfgang (Proc. Cracow Grid Workshop (CGW))

Multi-Level Comparison of Data Deduplication in a Backup Scenario - Meister, Dirk; Brinkmann, André (Proc. of the Israeli Experimental Systems Conference (SYSTOR))

Solution Patterns for the Development of Self-Optimizing Systems - Dumitrescu, Roman; Gausemeier, Jürgen; Dangelmaier, Wilhelm; Klöpper, Benjamin (Self-x in Engineering)

Control of the Pareto Optimality of Systems with Unknown Disturbances - Geisler, Jens; Trächtler, Ansgar (7th IEEE International Conference on Control & Automation (ICCA 2009))

Parametrische Modellreduktion für selbstoptimierende mechatronische Systeme - Krüger, Martin (Tagungsband Workshop GMA-Fachausschuß 1.30/1.40)

Control Strategy for the Lateral and Longitudinal Dynamics of a Fully Active X-by-wire Test Vehicle - Reinold, Peter; Nachtigal, Vitalij; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the European Control Conference 2009 (ECC))

Prototypische Applikation einer Vereinzelungsregelung an einem Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (Mechatronik 2009 VDI)

Entwicklung einer Hardware-in-the-Loop-Umgebung für den Steuergerätetest von Kondenstrocknern - Zeineldin, Tarek; Koert, Dirk; Löffler, Alexander; Trächtler, Ansgar (VDI Mechatronik)

RailCab Ein innovatives Schienenverkehrssystem für die Mobilität von morgen - Rustemeier, Carsten; Trächtler, Ansgar (Ingenieurspiegel Fachmagazin für Ingenieure)

Entwurf einer adaptiven Regelung für den Vereinzelungsvorgang in Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Aufbau und Regelung eines sturzvariablen Bahnfahrwerks mit Einzelradlenkung - Borsig, Michael; Trächtler, Ansgar; Geisler, Jens (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")